The Effect of Different Light Cure Systems on Microhardness of Bulk Fill Composite Materials - Linz A Shalan; Samer H. Thiab (College of Dentistry/ University of Baghdad, 2017)
Background: The aim of this study was to evaluate the effect of three types of light curing devices QTH, LED and Flashmax on the surface microhardness of three types of bulkfill composite resins; Filtek Bulkfill posterior composite ( 3M), Tetric Evo Ceram ( Ivoclar Vivadent) and Sonicfill composite ( Kerr) Materials and methods: Total number of 90 samples was prepared, 30 samples for each type of bulkfill composite, were divided into three main groups, group A: Filtek posterior bulkfil (3M), group B: Tetric Evo Ceram (Ivoclar Vivadent) and group C: contain Sonicfill composite (kerr). Which then divided into three subgroups (n= 10) (1) Samples cured by QTH system (2) Samples cured by LED system and (3) samples cured by Flashmax system then all samples were subjected for microhardness test (by Vickers hardness tester). The data were recorded and statistically analyzed, by the ANOVA and the Tukey test. Results: the data was subjected to statistical analysis using one way ANOVA and Tukey test, the result revealed that there was a high significant difference among the tested units with LED had high VHN values followed by QTH while Flashmax had lowest VHN values, also there was high significant difference among the tested materials in which Sonicfill composite had higher VHN value followed by Tetric EvoCeram while Filtek bulkfill posterior composite had the lowest VHN. Conclusions: microhardness of the composite resin materials depend upon energy of the curing device, time of exposure, composition of the composite material.